Geo-logic : breaking ground between philosophy and the earth sciences - Frodeman, Robert (SUNY series in environmental philosophy and ethics., 2003)
"Using a unified vision of geology, consisting of equal parts geo-poetry, geo-politics, geo-theology, and geo-science, Geo-Logic redraws the boundaries between philosophy and the earth sciences. Although each discipline makes crucial contributions to contemporary environmental concerns, neither will fulfill its potential until it transforms itself by engaging the other. This book offers examples of how to relate environmental philosophy to science, public policy, and real world problems, and shows what is epistemologically distinctive about scientific work and how to respond to the cultural dynamics that are pulling these issues into the public sphere. Frodeman advocates humanizing the earth sciences and bringing philosophy into the field."--Jacket